INCREASING STUDENTS’ VOCABULARY ACQUISITION BY MASTER AND MASTERY CARDS GAME - Venolia Sahrin; Mulyadi Hasan (Journal of Applied Linguistics and Literature, 2019)
The objective of this research is to explain how the Master and Mastery cards game improves students’ vocabulary acquisition and participation learning process of applying Master and Mastery cards game in teaching vocabulary for tenth-grade students of a vocational school. This research was carried out with a classroom action research design. Field notes were the instruments to collect the qualitative data. While the vocabulary test and gained the quantitative data that strengthen the quantitative data. The increasing of the test 1 and test 2 was 22.83 point. Responding to that result the teacher-researcher decided to stop the cycle at cycle two. According to the researcher and co-observer’s observation students participated actively while playing Master and Mastery vocabulary cards game. This research significantly increased students’ vocabulary acquisition as well as participation.